GE_GERICHTE C/7205/2014 vom 27. März 2015 - GE Cour de justice (2015)
MESURE PROVISIONNELLE; PROTECTION DE L'UNION CONJUGALE; GARDE ALTERNÉE | CPC.261; CC.176.3; CC.296.2: CC.301a.1; CC.302.1; CC.274.1